A Case Report on Sheehan's Syndrome - Pokharel, S; Jha, SC; Maskey, D; Shrestha, B; Poudel, P; Shrestha, B; Dhital, BM (Journal of Chitwan Medical College, 2013)
Sheehan’s syndrome is a well-known cause of panhypopituitarism secondary to pituitary apoplexy, that generally occurs after an intra- or postpartum bleeding episode characterized by massive hemorrhage and hypovolemic shock. The diagnosis can be difficult and is often formulated after some years from the syndrome occurrence. We report the case of a woman with a relatively early diagnosed Sheehan’s syndrome associated with amenorrhoea and secondary hypothyriodism complicated by postpartum hemorrhage. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8444 Journal of Chitwan Medical College Vol.3(2) 2013 49-50